Application of Scientific Advances to the Practice of forestry in India - Sagreiya, K. P. (Indian Forester, 1963)
This paper reviews the current trends in the practice of forestry, particularly relating to Silviculture (including Experimental Silviculture, Mensuration, Ecology, Soil Science and Forest Influences), Forest Genetics, Plant Physiology, Plant Introduction and Forest Protection (including Forest Entomology and Mycology). Silviculture: The technique of natural regeneration is based on ecological approach and plantation forestry is related to site classification, soil characteristics, climatic behaviour, soil moisture regime, mechanisation of routine operations, use of genetically superior planting stock, fertilization, irrigation, adoption of exotics, etc. Chemical control of weeds is being increasingly made. Fungoid and insect pests are being dealt by precautionery measures, hygienic fellings and biological control. Grazing is mainly controlled by dividing the forest into grazing units and fixing maximum incidence of cattle that may be grazed and periodically excluding grazing altogether. Fire protection is relied upon by cleaning fire lines during the critical period. Fire towers are being built and quick means of transport is being installed. A scheme to evolve the method of meteorological fire forecasts has been formulated. In easily accessible areas, management is of an intensive type, either as conversion to uniform system or clearfelling and planting. Around populated land, particularly in drier region, reliance is mainly placed on coppice growth and an efficient system of Coppice-with-Reserves has been evolved. In inaccessible and remote areas Selection-cum-Improvement method of working is still in vogue. Modern mechanised equipment is being used increasingly for reducing harvesting wastage and opening up hitherto locked up areas. Tree Physiology: Recent advances in tree physiology have materially contributed in shortening the exploitation age of forest species and in the induction of rooting by the use of hormones. These are important steps in speeding up breeding programmes and perpetuating improved forms by vegetative propagation. Role of water, light and nutrients in tree physiology has been assessed. Hormones and auxins have also been tried with advantage.